Pelatihan Pembuatan Penyedap Rasa dan Kerupuk melalui Pemanfaatan Limbah Kulit Udang dalam Upaya Peningkatan Ketahanan Pangan Keluarga - Flora, Rostika; Ningsih, Windi Indah Fajar; Yuliana, Indah; Ramdika, Sari Bema; Sari, Dwi Inda; Indahsari, Siti Rachmi; Suhendra, Ahmad Adi; Irawan, Purna (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2024)
Shrimp shells are not just waste but has many health and economic benefits. Shrimp is a marine product that is widely produced in Dusun Sembilang Banyuasin, but the people there do not know yet how to utilize and manage shrimp waste so that shrimp shells only become waste, pollute the environment and can cause disease. Therefore, it is necessary to transfer information regarding the utilization of shrimp shell waste. The method used in this community service is to provide training in the utilization of shrimp shell waste into flavorings and crackers with a target of 25 mothers. The purpose of this activity is so that shrimp shell waste can become a product that can be sold and become income for families so that it can increase family food security. This activity was part of the Kedaireka activity with partner PT Pertamina RU III which was carried out in July 2024 in Dusun Sembilang Banyuasin. The results of this activity were that the mothers were very enthusiastic in practicing making shrimp shells into flavorings and crackers. The flavoring from shrimp shells and shrimp shell crackers have a savory taste. Evaluation of this activity requires applied technology in drying shrimp skin and crackers because conventional drying (with the sun) is very dependent on the weather.